ASSESSMENT OF ANIMAL MODELS AS SURROGATES FOR HUMAN TUMORS FROM THREE DIFFERENT ORGANS - Farah, Ibrahim O; Arslan, Zikri; Tucci, Michelle; Benghuzzi, Hamed; Cameron, Joseph A (Biomedical sciences instrumentation, 2018)
The compositional balance and distribution of trace metals/elements in various body tissues are essential key players in tissue and cellular homeostasis. Low Zn levels as well as overexpression of metalothioneins were implicated in the development and progression of various cancers including the prostate. Nonetheless, wider elemental profiles that relate cancer and normal phenotypes with regards to metal homeostasis were not well elucidated in the literature. Moreover, laboratory animals are currently used as accepted models for studying cancer but the level of their representation of actual cancer tissues was not clear. This study is attempting to assess the relevance of animal models currently in use, as surrogates for cancer and establish their relationship to actual normal and cancer tissues from humans. The major focus of this study was to investigate the differential relationship of metal concentrations and profiles in cancer and normal tissues from cadavers of humans and their comparison to established animal models representing organ cancers. The working hypothesis was that elemental/metal concentrations and profiles seen in post mortem will show significant differences between normal and cancer-derived tissues as well as between various tissue types in humans, rats, and dogs. This study also establishes critical elemental/metal profiles that may be relevant in providing correlations with the development of three major cancers. Normal human and tumor tissues of cadaverous lung, breast, and liver used in this study were obtained from US Biomax Company and relevant animal models (Sprague-dawley and Brown Norwegian rats as well as dogs; were obtained from Jackson Laboratories and the Mississippi State Veterinary Laboratory in Pearl, MS), to analyze for elements and test the hypothesis. Tissue samples were prepared using standardized digestion procedures necessary for use with the Inductively Coupled Plasma-Atomic Emission mass Spectrometry (ICP-MS) to determine the concentrations and profiles of 21 elements including Ag, Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Na, Ni, Pb, Sb, Se, Sr, Tl, V, and Zn. Our data supports the notion that metal/elemental homeostasis is essential for normal tissue function and that elemental variations in content, distributions, and ranking are tissue specific as well as carcinoma and species-specific. Analysis of data showed significant variations in elemental content and distribution profiles/ranking between animal models and actual human tissues consistent with the hypothesis. It is concluded that elemental homeostasis is essential for normal tissue function and that shifts in their distribution and content are essential in determining the use of animal models as surrogates for studying cancer. These results are promising and warrant further studies to confirm the relevance of animal models in relation to their use as pre-clinical tools for examining targeted cancer therapeutics.